Artificial Intelligence in medicine: Potential and Application Possibilities - Comprehensive literature review - Kotowicz, Michał; Bieniak-Pentchev, Magdalena; Koczkodaj, Maria (Quality in Sport, 2025)
Artificial intelligence (AI) is transforming modern medicine by enhancing diagnostic accuracy, personalizing treatment, and streamlining clinical workflows. This literature review explores AI’s potential and practical applications across five key medical domains: psychiatry, ophthalmology, radiology, emergency medicine, and dermatology. In psychiatry, generative AI models support mental health through personalized interventions and symptom tracking, while in ophthalmology, multimodal learning improves early detection of eye diseases. Radiology benefits from AI-driven imaging analysis, increasing efficiency and diagnostic precision across various specialties, including neuroradiology and breast imaging. Emergency medicine sees promise in AI’s integration for rapid triage and decision support, though legal and interpretability challenges persist. In dermatology, AI enhances both aesthetic evaluations and diagnostic accuracy through advanced image recognition. Despite significant benefits, issues such as algorithmic bias, lack of transparency, and legal responsibility demand careful consideration. The review underscores the need for responsible implementation of AI systems that prioritize augmentation of human expertise rather than replacement.